MANAGEMENT OF LITERACY CULTURE DEVELOPMENT IN ELEMENTARY SCHOOLS - Maulida, Annisa; Suriansyah, Ahmad; Ngadimun (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2019)
The demand for knowledge plays a major role in the reading and writing ability of individuals towards an advanced generation. This study aims to describe the planning, organization, implementation, evaluation, and follow-up of literacy culture at SDN SN Sungai Miai 5 and 7 (National Standardized State Elementary Schools) in Banjarmasin. Data were collected through in-depth interviews, participatory observation, and documentation techniques, with its analysis carried out qualitatively. The results show that both schools have a good literacy culture and work together with residents to achieve the desired goals. It also shows a big influence on the achievements generated by the schools. It is hoped that the results of this study is used as material for consideration in implementing literacy culture development management in other schools.